Language assessment training in Hong Kong: Implications for language assessment literacy. (April 2015) - Lam, Ricky
Despite the call for using assessment to promote effective learning, most language teachers remain underprepared to conduct classroom-based formative assessment and interpret the summative assessment information for improving instruction as well as learning. Drawing upon a survey of programme and government documents, interviews, student assessment tasks, and teaching evaluation, this paper aims to explore the overall language assessment training landscape in five Hong Kong teacher education institutions against the backdrop of assessment reforms in primary/secondary school contexts. It specifically attempts to investigate the extent to which two assessment courses may facilitate and/or inhibit the development of pre-service teachers' language assessment literacy in one teacher education institution. Findings indicate that language assessment training in Hong Kong remains inadequate and selected language assessment courses are still unable to bridge the theory-practice gap within the assessment reform context. Implications and recommendations for promoting language assessment literacy are discussed.